A synonymous variant contributes to a rare Wiedemann-Rautenstrauch syndrome complicated with mild anemia via affecting pre-mRNA splicing - Peng, Qiongling; Zhang, Yan; Xian, Binqiang; Wu, Lianying; Ding, Jianying; Ding, Wuwu; Zhang, Xin; Ding, Bilan; Li, Ding; Wu, Jin; Hu, Xiaowu; Lu, Guanting (Frontiers in Molecular Neuroscience, 2022)
Wiedemann-Rautenstrauch syndrome (WDRTS) is an extremely rare autosomal recessive neonatal disorder. Currently, over 50 cases with variable phenotypes of WDRTS have been reported. In our cohort of prenatal and postnatal growth retardation, a female proband was found to have general growth retardation, neurocutaneous syndrome, and anemia. Karyotype test and array-CGH detected no obvious chromosomal aberrations. Trio-based whole-exome sequencing (Trio-WES) identified bi-allelic compound mutations in the coding sequence (CDS) of POLR3A gene (c.3342C>T, p.Ser1114= and c.3718G>A, p.Gly1240Ser). For the mild anemia phenotype, the underlying causal genetic factors could be attributed to the compound heterozygous mutations in FANCA gene (c.2832dup, p.Ala945CysfsTer6 and c.1902T>G, p.Asp634Glu). Mini-gene reporter assays revealed that the synonymous variant of POLR3A and the missense variant of FANCA could affect pre-mRNA splicing of each gene. For POLR3A, the synonymous mutation (c.3342C>T, p.Ser1114=) generated three types of aberrant isoforms. Therefore, the female patient was finally diagnosed as WDRTS caused by POLR3A. For FANCA, the missense variant (c.1902T>G, p.Asp634Glu) disrupted the normal splicing between exon 21 and 22, and produced two types of abnormal isoforms, one carrying the 1902G and the other spliced between exon 21 and 23 to exclude exon 22. Network analysis showed that POLR3A and FANCA could be STRINGed, indicating both proteins might collaborate for some unknown functions. Current investigation would broaden the knowledge for clinicians and genetic counselors and remind them to interpret those synonymous or predicted “benign” variants more carefully.